A incidência de desvios posturais em meninas de 6 a 17 anos da cidade de Novo Hamburgo - Cíntia Detsch; Claudia Tarrago Candotti (Universidade Federal do Rio Grande do Sul, 2001)
The objective of this study was to identify the incidence of postural deformity in students. Assessments of static posture, goniometrics and scapular measurements were mada in girls from 6 to 17 years old (n=154). The results indícate that the occurrence of postural deviation is common, specially from 10years old, when also starts to occur i righer percentage of asymmetry between the left and right sides of both the scapular and pelvic girths. The deformities most frequently observed were: anteriorization of the cervical spine (66,23%), protrusion of the shoulders (47,40%), scapular abduction (80,52%), dorsal kyphosis (10,39%), lombar lordosis (31,17%) and kypholordosis (29,22%).